استخدام الأشعة فوق البنفسجية موضعيا في علاج مرضى التهاب الأذن الوسطى القيحي المزمن مع الورم الكوليسترولي بعد عمليات حج الخشاء - يوسف, يوسف (Latakia University Journal -Medical Sciences Series, 2019)
لقد هدفت هذه الدراسة إلى تقييم تأثير الأشعة الفوق بنفسجية موضعيا على التئام الجوف الجراحي بعد عمليات حج الخشاء عند مرضى التهاب الأذن الوسطى القيحي المزمن مع الورم الكوليسترولي ، و ذلك عن طريق مراقبة التئام الجوف و مراحل تطور هذا الالتئام سريريا عيانيا و مجهريا و مخبريا و مقارنتها بطرق العلاج التقليدية . و قد تكونت مادة البحث من 55 مريض ما بين الأعوام( 1999-2004 ) من مراجعي العيادة الأذنية في مشفى الأسد الجامعي باللاذقية و الوحدة المهنية لأمراض الأذن و الأنف و الحنجرة و قد اجري لجميع هؤلاء المرضى عمليات حج خشاء جزري لمختلف درجاته و بعد العمل الجراحي في اليوم الرابع بعد نزع الدكة من الجوف تم تقسيم هؤلاء المرضى إلى مجموعتين: مجموعة أولى (1) تألفت من أربعين مريضا (40) عولجوا إضافة للطرق التقليدية موضعيا بالأشعة فوق البنفسجية بجلسة يومية بعدد عشر جلسات. والمجموعة الثانية (2) تألفت من(15) مريض اعتبرت مجموعة المقارنة و عولجت فقط بالطرق التقليدية وقد تم الحصول على النتائج التالية: عند المجموعة الأولى: الشفاء: عند 36 مريض % 90 (التئام كامل للجوف الجراحي وعدم حدوث النز خلال ثلاث سنوات بعد العمل الجراحي) التحسن: عند مريضين %5 (حصول النز من الجوف الجراحي في السنة الثانية بعد الجراحة) عدم التحسن: عند مريضين %5 ( حصول نز عدة مرات من الجوف الجراحي بعد فترة قصيرة من انتهاء المعالجة). عند المجموعة الثانية: الشفاء عند 11 مريض %73 التحسن : عند مريضين %13.3 عدم التحسن : عند مريضين %13.4 كما أن متوسط الفترة اللازمة للشفاء عند مرضى المجموعة الأولى كانت 15.6 يوم أما مرضى المجموعة الثانية فقد كان المتوسط 22.8 يوم. This study tries to assess the local effect of Ultra-Violet Rays on the healing of operation cavity of patients suffering of Chronic Suppura.tive Otitis Media with Cholesteatoma following radical mastadichtomy. This is done through observation of the operation cavity healing and its phases clinically, visually, microscopically and iaboratorilly. The study is conducted on 55 patients between 1999-2004 at AlAssad University Hospital, Lattakia. The patients were divided into two groups four days after the operation, when tampon was removed of cavity. Group one included 40 patients, who were given a daily session of local treatment through Ultra-Violet Rays for ten days in addition to traditional methods of treatments. Group two included I S patients, who were treated through traditional methods only for the purpose of a comparison, aiming at assessing the effectiveness of treatment by UltraViolet Rays. The study concludes that 36 patients of the first group (90%) were fully recovered and never suffered of any complications for three years after surgery; 2 patients (5%) improved, but suffered of puric discharge from cavity during the second year following operation; and 2 patients (5%) did not show any improvement and suffered several puric discharges shortly after surgery. As for the second group (comparison group), 11 patients (73%) fully recovered; 2 patients improved (13.3%); atid 2 patients (13.4%) did not show any improvement. The average period of recovery for the first group was 15.6 days, while it was 22.8 days for the second group.